Addition of amino acids modulates the in vitro digestibility of corn starch. (1st October 2022) - Yue, Shuke; Wang, Huaibin; Xu, Huixian; Liu, Hongsheng; Yu, Wenwen
Abstract: The addition of amino acids (AAs) including glycine (Gly), lysine (Lys) and glutamic acid (Glu) with different concentrations on starch morphological, physicochemical and in vitro digestion properties were studied. While AAs showed no effects on neither morphology nor crystalline characters, they all significantly influenced the starch relative crystallinity and swelling capacity in an order of Glu > Lys > Gly. For all samples, both fastly- and slowly- digestible starch fractions ( S F and S S ) were observed. While Glu and Gly increased S F content with a faster digestion rate, they reduced S S content with a slower digestion rate. On contrary, Lys reduced S F content and the digestion rate of S S . The inhibitory effects of AAs on starch retrogradation and enzyme activities, the acidic environment and Maillard reaction between starch phosphate monoester and Lys are responsible for altered starch digestibility. This study betters our understanding concerning how AAs interactions affect starch functional properties. Graphical abstract: Unlabelled Image